Réflexions Sur Les Variations Pluviométriques De La Région De Tiaret (Algérie Occidentale) Durant La Période 1984 – 2015 - Mohammed, Achir; Benchaben, Hellal (European Scientific Journal, ESJ, 2016)
The analysis of rainfall is offered over a period of thirty-two years of measurement. This study based on the calculation of a number of indices has to account for the extreme variability of rainfall in the region of Tiaret (western Algeria). It also shows the severe and lasting climate of drought observed in this region from 1984 to 2002. It also highlights the return to a wet phase recorded from 2003 to 2014. The year 2015 has been quite deficient in rainfall. Is it the beginning of a new period of drought?